Automated system for deploying operating systems using LAN (PXE SERVER) - I. V. Kendysh (Литьë и металлургия)
PXE is an environment for booting computers using a network card without using hard drives, CDs and other devices used while booting operating systems. By choosing a network boot in the BIOS, it is possible to install the OS / rid of viruses /recover disks /test RAM from the PXE Boot server. Such a tool is irreplaceable in the case of a large number of computers